Iron-oxidizing microorganisms affect the iron-bound organic carbon in the subsoil of alpine grassland during the thawing of seasonal frozen soil - Tian, Yuxin; Abulaizi, Maidinuer; Yang, Zailei; Kou, Tianle; Jia, Yuanbin; Hu, Yunpeng; Chen, Mo; Jia, Hongtao (Frontiers in Microbiology, 2025)
Iron (Fe) minerals possess a huge specific surface area and high adsorption affinity, usually considered as “rust tanks” of organic carbon (OC), playing an important role in global carbon storage. Microorganisms can change the chemical form of Fe by producing Fe-chelating agents such as side chains and form a stable complex with Fe(III), which makes it easier for microorganisms to use. However, in seasonal frozen soil thawing, the succession of soil Fe-cycling microbial communities and their coupling relationship with Fe oxides and Fe-bound organic carbon (Fe-OC) remains unclear. We characterized changes in the Fe phase, Fe-OC, Fe-oxidizing bacteria (FeOB), and Fe-reducing bacteria (FeRB) in the subsoil and analyzed the microbial mechanism underlying Fe-OC changes in alpine grassland by constructing a composite structural equation model (SEM). We found that the Fe(III) content consistently exceeded that of Fe(II). Among the three types of Fe oxides, organically complex Fe (Fep) decreased from 2.54 to 2.30 g·kg−1, whereas the opposite trend was observed for poorly crystalline Fe (Feo). The Fe-OC content also decreased (from 10.31 to 9.47 g·kg−1; p < 0.05). Fe-cycling microorganisms were markedly affected by the thawing of frozen soil (except FeRB). Fep and Feo directly affected changes in Fe-OC. Soil moisture (SM) and FeOB were significant indirect factors affecting Fe-OC changes. Freeze–thaw changes in the subsoil of alpine grassland in Central Asia significantly affected FeOB and Fe oxides, thus affecting the Fe-OC content. To the best of our knowledge, this was the first study to examine the influence of Fe-cycling microorganisms on the Fe phase and Fe-OC in the soil of alpine grassland in Central Asia. Overall, our findings provide scientific clues for exploring the biogeochemical cycle process in future climate change.